Physical processes controlling passive larval transport at the patagonian shelf break front - Franco, B. C, Palma, E., Combes, V., Lasta, M. L. (My University, 2017)
The largest beds of the Patagonian scallop (Zygochlamys patagonica) have been associated with high chlorophyll-a concentration observed along the Patagonian Shelf Break Front but there is no supported hypothesis about how this benthic-pelagic connection is maintained. In this work we address the main physical processes driving the benthic-pelagic linkages through oriented numerical experiments derived from a realistic, high-resolution numerical model, and Lagrangian stochastic simulations. The results support the hypothesis of an important dynamical control of the slope current on the fate of surface released passive particles and their subsequent bottom settlement. A high percentage of the particles released at the surface settled over the scallop beds. The particles remaining at the surface layer followed a prevailing NE flow direction with low cross-shelf dispersion. Additional experiments show that the secondary cross-shelf circulation forced by the slope current promotes downwelling and hence the settlement of particles on the westward side (onshore) of the shelf break. The percent of particles settling over the scallop beds exceeded 80% by the addition of vertical stochastic turbulence and tidal forcing. These results highlight the importance of including the vertical diffusivity in particle tracking experiments to better estimate benthic-pelagic interaction processes. Highlights •A high percentage of particles from the SBF settled inside of the scallop beds. •The main physical processes driving the benthic-pelagic processes are addressed. •Benthic-pelagic coupling is enhanced by the addition of vertical diffusivity. •The tidal forcing enhanced the vertical coupling in the Patagonian shelf break.
Keywords: Patagonian Shelf Break Front, Benthic-pelagic interaction, Stochastic processes, Patagonian scallop